Inspection method in bamboo roofs : assessment of the conservation conditions by using a drone and sensory analysis - Santos, Lara Monalisa Alves dos (2022)
The site inspection processes are sensorial and require technical knowledge. Accessing the roofs is the biggest challenge due to the risks for safety involved. The objective of this article is to propose a methodological procedure to evaluate the conservation conditions of four buildings located in Brasília, capital of Brazil, and to analyze the main anomalies existing in the bamboo roofing systems, their causes, and their maintenance needs. The site inspection standard recommended by ABNT NBR 16747:2020 were adopted for the sensory analysis. A drone was used for the acquisition of images showing anomalies. Pathologies were classified into five critical damage levels to inform the urgency of intervention needed in the systems.